Marketing and Pricing Strategies of Blockbuster Drugs in the South Korean Market: A 15-Year Retrospective Cohort Study for Choline Alfoscerate - Park, Jeewon; Bae, SeungJin; Lee, Tae-Jin; Son, Kyung-Bok (Frontiers in Pharmacology, 2020)
Introduction: Understanding marketing strategies and price competition among manufacturers is essential to manage health care expenditures, particularly those related to blockbuster drugs. Objectives: To assess marketing and pricing strategies of blockbuster drugs in South Korea. Methods: Baseline information on manufacturers who were granted marketing approval for choline alfoscerate in various forms were retrieved. Accumulation of manufacturers in the market were also identified, and manufacturers were categorized into first movers and latecomers based on their marketing time. Then, an event history analysis and a regression analysis were applied to estimate the duration of marketing and their price competition. Results: Currently, 109, 83, and 26 manufacturers produce choline alfoscerate in capsule, tablet, or syrup form, respectively, indicating that many manufacturers have marketed generics and the majority of the generics are categorized as latecomers. The size of the manufacturer was a significant factor in marketing new medicines, while the variable was not related to the marketing of modified drugs. Furthermore, price competition in the market was rare and only a few major firms initiated price competition. Conclusions: The Korean market appears to be an example of perfect competition when we focus on the number of manufacturers. However, the market is near-monopolistic when examining the price of generic drugs. While product competition between different forms of drugs is effective in lowering price, product competition within the same form of a drug does not exist in the market.